Tuning the electronic properties at the surface of BaBiO3 thin films - Ferreyra, Cristian Daniel (2016)
The presence of 2D electron gases at surfaces or interfaces in oxide thin films remains a hot topic in condensed matter physics. In particular, BaBiO3 appears as  a very interesting system as it was theoretically proposed that its (001) surface should become metallic if a Bi-termination is achieved (Vildosola et al., PRL 110, 206805 (2013)). Here we report on the preparation by pulsed laser depositionand characterization of BaBiO3 thin films on silicon. We show that the texture of the films can be tuned by controlling the growth conditions, being possible to stabilize strongly (100)-textured films. We find significant differences on the spec- troscopic and transport properties between (100)-textured and non-textured films.We rationalize these experimental results by performing first principles calcula- tions, which indicate the existence of electron doping at the (100) surface. This stabilizes Bi ions in a 3+ state, shortens Bi-O bonds and reduces the electronic band gap, increasing the surface conductivity. Our results emphasize the importance of surface effects on the electronic properties of perovskites, and provide strategies to design novel oxide heterostructures with potential interface-related 2D electron gases. C 2016 Author(s). All article content, except where other- wise noted, is licensed under a Creative Commons Attribution (CC BY) license